Cropland change analysis in Zhejiang coastal region - DING Han; WANG Ren-chao (浙江大学学报. 农业与生命科学版)
In order to detect the cropland changes and its drivers in Zhejiang Province coastal region, TM and ETM + images in 1985, 1993 and 2001 were used. A stratified unsupervised classification technique in conjunction with visual interpretation was performed, and an overall classification accuracy of 85% was achieved. The study presented cropland decreased 264036 hm2 among the 16 years and the decreased cropland almost converted to urban or built-up. The amount of decreasing cropland from 1993 to 2001 was more than that from 1985 to 1993 in the most towns of study area. All in all, cropland decreasing was different in different places and different times, and landuse of the agriculture and other department must be supervised by the total plan of landuse in order to sustainable development.